2006
DOI: 10.1055/s-2006-955089
|View full text |Cite
|
Sign up to set email alerts
|

Arabinoxylan Fibre Consumption Improved Glucose Metabolism, but did not Affect Serum Adipokines in Subjects with Impaired Glucose Tolerance

Abstract: The consumption of arabinoxylan, a soluble fibre fraction, has been shown to improve glycemic control in type 2 diabetic subjects. Soluble dietary fibre may modulate gastrointestinal or adipose tissue hormones regulating food intake. The present study investigated the effects of arabinoxylan consumption on serum glucose, insulin, lipids, leptin, adiponectin and resistin in subjects with impaired glucose tolerance. In a randomized, single-blind, controlled, crossover intervention trial, 11 adults consumed white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 45 publications
4
36
1
Order By: Relevance
“…↓ glucose response area after the meal Bread containing 0, 6 or 12 g of AX 3 breakfasts on 3 days ↓ postprandial glycaemia, improvement in the insulin response [104] 15 individuals with type 2 diabetes; randomised crossover intervention Bread and muffins containing 14% AX for 5 weeks ↓ fasting glycaemia, ↓ glycaemia and insulinaemia 2 h post OGTT [105] 11 individuals with impaired glucose tolerance; single-blind, controlled, crossover intervention over 18 weeks 15 g AX supplied daily via bread and powder for 6 weeks, followed by a 6 week washout period ↓ fasting glycaemia, = insulin, After LMCT: ↓postprandial glycaemia, ↓ insulin [106,107] 15 healthy individuals; crossover intervention GIP, glucose-dependent insulinotropic polypeptide; LMCT, liquid meal challenge test; MCP-1; monocyte chemoattractant protein-1; = means no significant changes vs controls…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 99%
“…↓ glucose response area after the meal Bread containing 0, 6 or 12 g of AX 3 breakfasts on 3 days ↓ postprandial glycaemia, improvement in the insulin response [104] 15 individuals with type 2 diabetes; randomised crossover intervention Bread and muffins containing 14% AX for 5 weeks ↓ fasting glycaemia, ↓ glycaemia and insulinaemia 2 h post OGTT [105] 11 individuals with impaired glucose tolerance; single-blind, controlled, crossover intervention over 18 weeks 15 g AX supplied daily via bread and powder for 6 weeks, followed by a 6 week washout period ↓ fasting glycaemia, = insulin, After LMCT: ↓postprandial glycaemia, ↓ insulin [106,107] 15 healthy individuals; crossover intervention GIP, glucose-dependent insulinotropic polypeptide; LMCT, liquid meal challenge test; MCP-1; monocyte chemoattractant protein-1; = means no significant changes vs controls…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 99%
“…In fact, isolation of aleurone from wheat bran resulted in considerable differences in the degrees of branching in AX [22][23][24]. The physiological effect of AX is largely unknown but several studies indicate that they behave like a rapidly fermentable, soluble fiber in the colon with impact on lipid and glucose metabolism in human and/or in rats [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen randomised controlled trials were identified that presented evidence on isolated gums and gelling agents in relation to fasting blood lipids (Bell et al, 1990;Ryle et al, 1990;Landin et al, 1992;Vido et al, 1993;Mee & Gee, 1997;Pasman et al, 1997b;Panlasigui et al, 2003;Marett & Slavin, 2004;Lehtimaki et al, 2005;Schwab et al, 2006;Garcia et al, 2006;Wood et al, 2007;Reppas et al, 2009) Two trials could not be included in meta-analysis (Vido et al, 1993;Pasman et al, 1997b), but demonstrated no significant effect of fibre isolates and gum supplements on fasting blood lipids. One trial only provided data for fasting triacylglycerol concentration (Landin et al, 1992).…”
Section: Mixed Isolated Fibre Interventionsmentioning
confidence: 99%
“…One trial could not be included in meta-analysis as it did not report the necessary data, but demonstrated no significant effect of soluble fibre isolates in relation to fasting blood glucose (Pasman et al, 1997a Fasting blood insulin A5.30. Eight publications relating to seven randomised controlled trials were identified that presented evidence fibre isolates and gum supplements in relation to fasting insulin (Ryle et al, 1990;Landin et al, 1992;Pasman et al, 1997a;Marett & Slavin, 2004;Schwab et al, 2006;Garcia et al, 2006;Wood et al, 2007;Garcia et al, 2007). Two papers presented evidence from one trial (Garcia et al, 2006;Garcia et al, 2007).…”
Section: Eating Motivationmentioning
confidence: 99%